2017
DOI: 10.5194/se-2017-116
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of sewage irrigation on soil properties of farmland in China: A review

Abstract: Abstract:Fresh water is a valuable nonrenewable resource and plays an important role of maintaining

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Wastewater may contain unwanted pathogens and chemical constituents that pose health and environmental risks. The negative effects of crop irrigation with wastewater are primarily due to the presence of high total suspended and dissolved solids, high nutrient contents, and PTEs [ 3 , 4 , 16 , 56 ]. Wastewater may contain high concentrations of salts which can affect the soil quality and productivity by accumulating in the root zone.…”
Section: Potential Impacts Of Wastewater Irrigation On Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wastewater may contain unwanted pathogens and chemical constituents that pose health and environmental risks. The negative effects of crop irrigation with wastewater are primarily due to the presence of high total suspended and dissolved solids, high nutrient contents, and PTEs [ 3 , 4 , 16 , 56 ]. Wastewater may contain high concentrations of salts which can affect the soil quality and productivity by accumulating in the root zone.…”
Section: Potential Impacts Of Wastewater Irrigation On Cropsmentioning
confidence: 99%
“…Wastewater contains potentially toxic elements (PTEs) such as zinc, chromium, copper, cadmium, nickel, lead, mercury, and parasitic worms, which can induce severe risks to the human health and the environment [ 13 , 14 , 15 ]. The use of untreated wastewater for crop irrigation can also cause soil hardening and shallow groundwater contamination [ 16 , 17 ]. However, the main problem of wastewater crop irrigation is the presence of potentially toxic elements (PTEs) [ 4 , 18 , 19 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [78] during their studies found that water holding capacity, soil bulk density, porosity, permeability, infiltration besides other factors also depends on the concentration of potentially toxic elements. Soil chemical properties depend on soil pH which affects the availability of soil nutrients and form of potentially toxic elements.…”
Section: Effects Of Potentially Toxic Elements On Soil Physicochemicamentioning
confidence: 99%
“…Most of the studies indicated that haze had led to decreased crop production, reduced the quality of agricultural products, environment of agricultural production pollution, and circulation of agricultural products hindering [20][21][22], among which particle matter is the "culprit", especially PM2.5. Different plants showed different responses to PM2.5, which deserved further investigation.…”
Section: The Impacts Of Haze On Plantsmentioning
confidence: 99%